Developing dual and specific inhibitors of dimethylarginine dimethylaminohydrolase-1 and nitric oxide synthase: Toward a targeted polypharmacology to control nitric oxide - Wang, Yun (2009)
Molecules that block nitric oxide's (NO) biosynthesis are of significant interest. For example, nitric oxide synthase (NOS) inhibitors have been suggested as anti-tumor therapeutics, as have inhibitors of dimethylarginine dimethylaminohydrolase (DDAH), an enzyme that catabolizes endogenous NOS inhibitors. Dual-targeted inhibitors hold promise as more effective reagents to block NO biosynthesis than single-targeted compounds. In this study, a small set of known NOS inhibitors are surveyed as inhibitors of recombinant human DDAH-1. From these, an alkylamidine scaffold is selected for homologation. Stepwise lengthening of one substituent converts an NOS-selective inhibitor into a dual-targeted NOS/DDAH-1 inhibitor and then into a DDAH-1 selective inhibitor, as seen in the inhibition constants of N(5)-(1-iminoethyl)-, N(5)-(1-iminopropyl)-, N(5)-(1-iminopentyl)- and N(5)-(1-iminohexyl)-l-ornithine for neuronal NOS (1.7, 3, 20, >1,900 μM, respectively) and DDAH-1 (990, 52, 7.5, 110 μM, respectively). A 1.9Å X-ray crystal structure of the N(5)-(1-iminopropyl)-l-ornithine : DDAH-1 complex indicates covalent bond formation between the inhibitor's amidino carbon and the active-site Cys274, and solution studies show reversible competitive inhibition, consistent with a reversible covalent mode of DDAH inhibition by alkylamidine inhibitors. These represent a versatile scaffold for the development of a targeted polypharmacological approach to control NO biosynthesis.